2017
DOI: 10.1007/s00441-017-2653-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential cellular immune response of Galleria mellonella to Actinobacillus pleuropneumoniae

Abstract: In the present work, we have investigate the cellular immune response of Galleria mellonella larvae against three strains of the gram-negative bacterium Actinobacillus pleuropneumoniae: low-virulence (780), high-virulence (1022) and the serotype 8 reference strain (R8). Prohemocytes, plasmatocytes, granulocytes, oenocytoids and spherulocytes were distinguished according to their size and morphology, their molecular markers and dye-staining properties and their role in the immune response. Total hemocyte count,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 68 publications
3
20
0
Order By: Relevance
“…In the present study, the level of NBR1 protein was found to be elevated in wax moth hemolymph after fungal invasion, while p62 protein level remained stable, even after infection (Fig 8); it is possible that autophagy took place without the need for p62 protein. Our results confirm those of previous studies showing that hemocytes of wax moth induce the autophagic pathway [44,57]. Further evidence that these two processes might interact and coincide with each other was given by Mizerska-Dudka and Andrejko (2014), who observed features typical for both apoptosis and autophagy in wax moth hemocytes following Pseudomonas aeruginosa infection.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the level of NBR1 protein was found to be elevated in wax moth hemolymph after fungal invasion, while p62 protein level remained stable, even after infection (Fig 8); it is possible that autophagy took place without the need for p62 protein. Our results confirm those of previous studies showing that hemocytes of wax moth induce the autophagic pathway [44,57]. Further evidence that these two processes might interact and coincide with each other was given by Mizerska-Dudka and Andrejko (2014), who observed features typical for both apoptosis and autophagy in wax moth hemocytes following Pseudomonas aeruginosa infection.…”
Section: Discussionsupporting
confidence: 92%
“…The numbers of colony-forming units (CFU) were counted after 48 h of incubation at 30ºC. The experiments were repeated twice and representative experiments are presented.The THC in the hemolymph of G. mellonella larvae were assayed using a protocol fromBlanco et al (2017). The experiment was performed with 3 larvae for each test condition.…”
mentioning
confidence: 99%
“…It was observed that the percentage of plasmocytes tends to increase with respect to the other four hemocyte classes. This may be due to the fact that these cells are responsible for adherence and phagocytosis, which is the main antifungal immune response, and also that these cells participated in nodule formation (Arteaga Blanco et al, 2017;Boguś et al, 2018;Pereira et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The hemolymph drop was then spread over and stained with Wright's stain. According to previous reports (Arteaga Blanco et al, 2017;Wojda, 2017;Boguś et al, 2018), hemocytes were characterized and counted under a light Leica DM500 microscope.…”
Section: Characterization Of Hemocytesmentioning
confidence: 99%
See 1 more Smart Citation